1998
DOI: 10.1093/emboj/17.15.4274
|View full text |Cite
|
Sign up to set email alerts
|

A novel capacitative calcium entry channel expressed in excitable cells

Abstract: In addition to voltage-gated calcium influx, capacitative calcium entry (CCE) represents a major pathway for calcium entry into the cell. Here we report the structure, expression and functional properties of a novel CCE channel, TRP5. This channel is a member of a new subfamily of mammalian homologues of the Drosophila transient receptor potential (TRP) protein, now comprising TRP5 (also CCE2) and the structurally related CCE1 (also TRP4). Like TRP4, TRP5 forms ion channels mainly permeable for Ca 2⍣ which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
217
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(230 citation statements)
references
References 55 publications
9
217
2
1
Order By: Relevance
“…Whereas TRPC4 and TRPC5 were activated by an unknown PLC-dependent mechanism (8, 9), TRPC1 was characterized as a SOC (10). Other studies indicated that TRPC3, TRPC4, and TRPC5 might also contribute to SOCs activated by depletion of intracellular Ca 2ϩ stores (11)(12)(13)(14).Based on their structural similarity with voltage-dependent K ϩ channels, functional TRPC complexes are presumed to be tetramers. Many of the disparate results regarding TRPC function and regulation could be reconciled by assuming that TRPC subunits can assemble into heteromeric channels with diverse properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas TRPC4 and TRPC5 were activated by an unknown PLC-dependent mechanism (8, 9), TRPC1 was characterized as a SOC (10). Other studies indicated that TRPC3, TRPC4, and TRPC5 might also contribute to SOCs activated by depletion of intracellular Ca 2ϩ stores (11)(12)(13)(14).Based on their structural similarity with voltage-dependent K ϩ channels, functional TRPC complexes are presumed to be tetramers. Many of the disparate results regarding TRPC function and regulation could be reconciled by assuming that TRPC subunits can assemble into heteromeric channels with diverse properties.…”
mentioning
confidence: 99%
“…Whereas TRPC4 and TRPC5 were activated by an unknown PLC-dependent mechanism (8, 9), TRPC1 was characterized as a SOC (10). Other studies indicated that TRPC3, TRPC4, and TRPC5 might also contribute to SOCs activated by depletion of intracellular Ca 2ϩ stores (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Recent investigations have extensively studied the regulation of TRPC channel activity. TRPC1, -4, and -5 appear to be activated through a store-operated mechanism (7)(8)(9). TRPC3 and TRPC1 are physically associated with IP 3 receptors (10 -13) and ryanodine receptors (14) and are activated when a gated conformational change in the IP 3 receptors or ryanodine receptors is sensed.…”
mentioning
confidence: 99%
“…The initial hypothesis of TRPC species (canonical mammalian TRP homologs) representing the structural basis of the ubiquitous Ca 2+ entry pathway termed capacitative-(CCE) or store-operated Ca 2+ entry (SOCE), which replenishes cellular Ca 2+ stores after intracellular Ca 2+ mobilization, Zhu et al 1996;Zitt et al 1996;Philipp et al 1998), was questioned or contradicted in many follow-up studies (Zitt et al 1997;Sinkins et al 1998;Zhu et al 1998;McKay et al 2000;Schaefer et al 2000). The prominent approach used in these investigations was heterologous expression of a single TRPC species in cellular systems that have proven suitable for analysis of ion channel function.…”
Section: Introductionmentioning
confidence: 99%